2014
DOI: 10.1097/scs.0000000000000643
|View full text |Cite
|
Sign up to set email alerts
|

Extradural Abscess Secondary to Salmonella enteritidis in a Child Following Fronto-orbital Facial Advancement and Remodeling Surgery

Abstract: Intracranial infections caused by Salmonella are rare. We describe the first case of a child undergoing craniofacial surgery for trigonocephaly and subsequently developing an extradural abscess secondary to likely community-acquired Salmonella enteritidis. He underwent surgical washout but returned to theater for a further 2, alongside a prolonged course of intravenous ciprofloxacin. We observed extensive anterior skull bone loss at 78 days postoperatively. At 1 year 11 months, extensive anterior skull bone re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Another report describes a 17-month-old with nontyphoidal salmonella who had three days of diarrheal illness and recent head trauma followed by extradural abscess formation, but our patient did not have any notable trauma to increase the risk for abscess and osteomyelitis [ 7 ]. Other reports have described central nervous system salmonella abscess in a 12-month-old and 26-month-old following neurosurgical procedures [ 8 , 9 ]. There are various reports of salmonella osteomyelitis in teenagers and older children, who tend to have far more of the typical exposure and individual risk factors than our patient [ 5 , 10 - 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another report describes a 17-month-old with nontyphoidal salmonella who had three days of diarrheal illness and recent head trauma followed by extradural abscess formation, but our patient did not have any notable trauma to increase the risk for abscess and osteomyelitis [ 7 ]. Other reports have described central nervous system salmonella abscess in a 12-month-old and 26-month-old following neurosurgical procedures [ 8 , 9 ]. There are various reports of salmonella osteomyelitis in teenagers and older children, who tend to have far more of the typical exposure and individual risk factors than our patient [ 5 , 10 - 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gradual expansion of the cranium and the surrounding soft tissue allows greater increase of the intracranial volume than 1-stage cranioplasty. Moreover, because bone flaps are not dissected from dura and blood supply to bone flaps is preserved, early bone formation and good cranial growth as well as reduced risk of extradural abscess 16 are anticipated after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…While a variety of studies have cataloged infections and mortality in pediatric and craniofacial surgery there is a paucity of literature detailing the management of potentially life-changing deep space infections. [5][6][7][8][9][10][11][12][13][14] While recent studies highlight the incidence of infections they provide little specific detail regarding the severity or location of these infections. 3 Yeung et al in their retrospective study, found that complicated diagnoses were associated with a higher risk of surgical site infection, as some of the patients had to go through multiple procedures.…”
Section: Introductionmentioning
confidence: 99%